2017
DOI: 10.1002/aelm.201700221
|View full text |Cite
|
Sign up to set email alerts
|

Highly Stable Indium‐Gallium‐Zinc‐Oxide Thin‐Film Transistors on Deformable Softening Polymer Substrates

Abstract: more complex applications that more closely mimic the behavior and size scale of biology. To these ends, bioelectronic devices must demonstrate several critical features: be manufacturable via a repeatable fabrication processes; exhibit resistance to mechanical deformation; and demonstrate electrical reliability.Technologies based on TFTs allowed the microfabrication of large-area applications such as flat-panel displays, which were difficult to develop on flexible substrates due to their high temperature proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 53 publications
0
20
0
Order By: Relevance
“…The electrode showed at least 10× reduction in electrochemical impedance, ~7% transmittance improvement, and stability after over 600 cycles of mechanical bending (Yang et al, 2019b ). Other semiconducting materials, such as germanium (Ge), silicon germanium alloy (SiGe), indium-doped zinc oxide (IZO), indium-gallium-zinc oxide (a-IGZO), and zinc oxide (ZnO), has also been investigated as recording electrode materials because of their desired electrical, mechanical, optical, biocompatible, and stable/biodegradable properties (Gao et al, 2012 ; Dagdeviren et al, 2013 ; Lee et al, 2015 ; Gutierrez-Heredia et al, 2017 ; Mao et al, 2018 ; Huerta et al, 2019 ).…”
Section: Electrode Materialsmentioning
confidence: 99%
“…The electrode showed at least 10× reduction in electrochemical impedance, ~7% transmittance improvement, and stability after over 600 cycles of mechanical bending (Yang et al, 2019b ). Other semiconducting materials, such as germanium (Ge), silicon germanium alloy (SiGe), indium-doped zinc oxide (IZO), indium-gallium-zinc oxide (a-IGZO), and zinc oxide (ZnO), has also been investigated as recording electrode materials because of their desired electrical, mechanical, optical, biocompatible, and stable/biodegradable properties (Gao et al, 2012 ; Dagdeviren et al, 2013 ; Lee et al, 2015 ; Gutierrez-Heredia et al, 2017 ; Mao et al, 2018 ; Huerta et al, 2019 ).…”
Section: Electrode Materialsmentioning
confidence: 99%
“…A previous study demonstrated that even with a 5 µm thick polymer encapsulation layer, IGZO thin-film transistors fabricated on the same softening polymer substrate endured bending stresses up to 10 000 cycles. [22] Finally, the high-frequency properties of the Schottky diodes were characterized by one-port scattering parameter measurements. Figure 6a shows representative impedance spectra obtained from a 100 µm × 100 µm Schottky diode fabricated on the softening polymer substrate, demonstrating a cutoff frequency (f c ) of ≈1 GHz at 0 V bias.…”
Section: Wwwadvelectronicmatdementioning
confidence: 99%
“…morphous oxide semiconductor TFTs, due to their moderate mobility, low cost, large size uniformity, high transparency, and excellent flexibility, have been widely used in applications from large-scale display to flexible portable devices [1][2][3][4][5][6][7][8][9][10][11][12][13]. In addition, because of a low process temperature and extremely low off-state current (I off ), they have tremendous promise in emerging applications, including internet of things (IoT), monolithic three-dimensional (3D) integrated nano-electronic, and photonic systems [14][15][16][17], where low power and high performance are highly desired.…”
Section: Introductionmentioning
confidence: 99%